Pendampingan UMKM Bumdes Edu Wisata untuk Meningkatkan Kapasitas Wirausaha di Desa Hendrosari Kecamatan Menganti Kabupaten Gresik - Kurniawan, Tri; Nusantara, Widya (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
This research aims to describe the assistance to MSMEs by BUMDes Edu Wisata Lontar Sewu to increase entrepreneurial capacity. Indicators of accompanying roles are facilitative roles, learning roles, representational roles and technical roles, while indicators of increasing capacity in entrepreneurship include technological dimensions, labor dimensions, technological dimensions. The type of research used is descriptive qualitative. The subjects of this research are the Head of BUMDes Edu Wisata and six MSME actors. Data collection techniques are observation, interviews and documentation. Data analysis techniques consist of reduction, data alignment and drawing conclusions. Then data validity was carried out to increase the degree of trust in the data obtained in the field by triangulating the sources. The results of the research show that BUMDes carry out four roles, namely 1) facilitative role 2) learning role 3) representational role and 4) technical role. Through the assistance provided by BUMDes Edu Wisata Lontar Sewu to MSME actors, various entrepreneurial capacity improvements can be identified, namely 1) Dimensions workforce, 2) Technological dimension.